Avascular necrosis of femoral head: a rare case as a symptom of the chronic phase in adult chronic myelogenous leukemia patients on nilotinib therapy - Mahayanti, Ni Kadek Seri; Budiyasa, Dewa Gde Agung (International Journal of Advances in Medicine, 2023)
Chronic myelogenous leukemia (CML) is a malignant clonal disorder of hematopoietic stem cells characterized by abnormal proliferation and accumulation of immature granulocytes. Avascular necrosis (AVN) is a rare case in CML patients where a systematic review reported only 21 cases from 1984 to 2021 of which 17 cases were AVN of the femoral head (AVNFH) and 3 cases were associated with treatment with tyrosine kinase inhibitors, namely imatinib, desatinib and nilotinib. We report a 51-year-old male patient with complaints of hip joint pain. The patient was diagnosed with CML from bone marrow examination with hypercellular results and PCR examination which detected the presence of BCR-ABL transcription in the form of b2a2 fusion. The patient received nilotinib 200 mg every 12 hours. The diagnosis of AVN was established from clinical symptoms and radiological examination. The patient was planned to undergo a total hip replacement.